Expression and Processing of Amyloid Precursor Protein in Vascular Endothelium - d'Uscio, Livius V. (Physiology (Bethesda), 2016)
Amyloid precursor protein (APP) is evolutionary conserved protein expressed in endothelial cells of cerebral and peripheral arteries. In this review, we discuss mechanisms responsible for expression and proteolytic cleavage of APP in endothelial cells. We focus on physiological and pathological implications of APP expression in vascular endothelium.